Voltage hysteresis model for silicon electrodes for lithium ion batteries, including multi-step phase transformations, crystallization and amorphization - Jiang,Y; Offer,GJ; Jiang,J; Marinescu,M; Wang,H (Journal of the Electrochemical Society, 2020)
Silicon has been an attractive alternative to graphite as an anode material in lithium-ion batteries (LIBs). The development of better silicon electrodes and the optimization of their operating conditions for longer cycle life require a quantitative understanding of the lithiation/delithiation mechanisms of silicon and how they are linked to the electrode behaviors. Herein we present a zero-dimensional mechanistic model of silicon anodes in LIBs. The model, for the first time, quantitatively accounts for the multi-step phase transformations, crystallization and amorphization of different lithium-silicon phases during cycling while being able to capture the electrode behaviors under different lithiation depths. Based on the model, a linkage between the underlying reaction processes and electrochemical performance is established. In particular, the two sloping voltage plateaus at low lithiation depth are correlated with two electrochemical phase transformations and the emergence of the single broad plateau at high lithiation depth is correlated with the amorphization of c-Li15Si4. The model is then used to study the effects of crystallization rate and surface energy barriers, which clarifies the role of surface energy and particle size in determining the performance behaviors of silicon. The model is a necessary tool for future design and development of high-energy-density, longer-life silicon-based LIBs.